2017
DOI: 10.1039/c7qm00319f
|View full text |Cite
|
Sign up to set email alerts
|

New method for the synthesis of a highly-conjugated acene material and its application in Perovskite solar cells

Abstract: Kita-type coupling and Scholl-type oxidative cyclodehydrogenation to afford acene from binaphthalene and mesitylene is as an effective alternative to the reported approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moreover, Huang et al applied graphdiyne to modify PC 61 BM and improved the film conductivity and interfacial coverage of ETL . Jia et al employed acene to modified PC 61 BM and a PCE of 17.07% could be achieved . Lin et al reported that indene-C 60 bisadduct was employed to replace PC 61 BM for its higher LUMO level and a high PCE of 18.5% could be obtained .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Huang et al applied graphdiyne to modify PC 61 BM and improved the film conductivity and interfacial coverage of ETL . Jia et al employed acene to modified PC 61 BM and a PCE of 17.07% could be achieved . Lin et al reported that indene-C 60 bisadduct was employed to replace PC 61 BM for its higher LUMO level and a high PCE of 18.5% could be obtained .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the prepared precursors 175a and 175b were subjected to reaction with FeCl 3 (oxidant and Lewis acid) to form promising products 176a and 176b in good yields ( Scheme 74 ). 105 …”
Section: Synthetic Strategies Toward Nanographenes By Reagent-mediate...mentioning
confidence: 99%
“…The thermodynamic possibility of the electron transfer in dyads with a MPX/MPcX donor part was evaluated using a ΔG CS parameter (the free-energy change for charge separation) that was obtained by cyclic voltammetry for (ImF)CoPc(3,5-di-t BuPhO) 8 /(AcO)(ImF) MnPc(3,5-di-t BuPhO) 8 and (PyF) 2 CoP (2,3,7,8,12,18)hexa-Me-13,17-di-Et-5-(Py-2-yl) in the 0.1 M (n-Bu) 4 NClO 4 solution in dichloromethane. [117,120] The corresponding ΔG CS values are −0.22/−0.07 and −0.72 eV.…”
Section: The Relevance Of Mpxs For Sm-oscsmentioning
confidence: 99%
“…The design and preparation of new conjugated molecules is one of the research topics in the science of molecular materials developed firstly as chemical physics of molecular conducting materials and then expanded on molecular optoelectronics and bioelectronics. [1][2][3] A planar structure and an ideal aromatic system are inherent in porphine molecules and their numerous derivatives. However, of great interest for the application as molecular materials are porphyrins predominantly in the form of metal derivatives due to the advent of new unique properties by the combination of metal atom and macrocycle electronic systems in one molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation